Journalists' Perceptions of the Journalist Competency Test in the Context of Professionalism in East Java, Indonesia - Syafiuddin, Muhammad; Suratnoadji, Catur; Claretta, Dyva (International Journal of Social Science, Education, Communication and Economics, 2025)
This study aims to understand journalists' perceptions of the journalist competency test set by the Press Council as a standard of professionalism in the Indonesian press. Using a qualitative approach with a phenomenological method, this study involved five journalists in East Java, comprising three certified journalists and two who declined to participate in the competency test process. The data collected was analyzed using NVivo 15 software. The results showed that some journalists perceived the competency test as an administrative formality that did not guarantee competence and professionalism. The competency test also has no impact on their careers or welfare. However, informants stated that if carried out consistently and professionally, the competency test has the potential to fence press freedom from unethical practices and strengthen journalistic quality. This research also emphasizes the importance of revamping regulations and maintaining the Press Council in the implementation of journalist competency tests.